2017
DOI: 10.1080/13548506.2017.1418014
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination and predictor variables among a group of dental students in Turkey

Abstract: The aim of this study was to assess the prevalence of procrastination among a group of Turkish dental students and to determine the predictors and consequences of procrastination. A total number of 273 females and 179 males (aged between 18 and 28) were included in the study. Tuckman procrastination scale, Academic Life Satisfaction Scale, Concern over Mistake Scale, Poor Time Management Scale, Self-Doubt Scale, Irrational Beliefs about Studying Scale, Positive and Negative Affect Schedule and Life Satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
4
22
0
1
Order By: Relevance
“…This confirmed the findings of numerous previous studies (e.g., Kohama, 2010). Fear of failure is mentioned as a reason for procrastination behavior (Atalayin, Balkis, Tezel, & Kayrak, 2017). Thus, it could be supposed that dental students engaged in procrastination behavior because of anxiety about failing course examinations.…”
Section: The Mechanism Underlying Academic Performancesupporting
confidence: 90%
“…This confirmed the findings of numerous previous studies (e.g., Kohama, 2010). Fear of failure is mentioned as a reason for procrastination behavior (Atalayin, Balkis, Tezel, & Kayrak, 2017). Thus, it could be supposed that dental students engaged in procrastination behavior because of anxiety about failing course examinations.…”
Section: The Mechanism Underlying Academic Performancesupporting
confidence: 90%
“…Limited information could be found in the literature regarding class rank or GPA at tertiary education as an antecedent of life satisfaction. A cross-sectional study of Turkish dental students showed that SWLS score may be positively associated with their academic performance [33]. We demonstrated that the specialists who were ranked in the upper middle quartile (26 to 50%), but interestingly not top 25%, of their class in dental school had a significantly higher mean life satisfaction score than those in the bottom 25% of the class.…”
Section: Discussionmentioning
confidence: 66%
“…[ 12 ] However, gender differences related to procrastination have been inconsistent ranging from weak to nonexistent. [ 8 26 27 ] Studies have reported a greater level of procrastination among male students, due to task aversiveness, poor time management, and less sincerity toward their study. [ 11 13 ] Lower procrastination among females has been attributed to behavioral self-control and time management leading to lesser procrastination.…”
Section: Discussionmentioning
confidence: 99%